The Beauty is a beast: Does leachate from the invasive terrestrial plant Impatiens glandulifera affect aquatic food webs?. Issue 4 (6th April 2022) - Diller, Jens G. P.; Drescher, Sophia; Hofmann, Mario; Rabus, Max; Feldhaar, Heike; Laforsch, Christian
Abstract: Invasive alien species are a major threat to ecosystems. Invasive terrestrial plants can produce allelochemicals which suppress native terrestrial biodiversity. However, it is not known if leached allelochemicals from invasive plants growing in riparian zones, such as Impatiens glandulifera, also affect freshwater ecosystems. We used mesocosms and laboratory experiments to test the impact of I. glandulifera on a simplified freshwater food web. Our mesocosm experiments show that leachate from I. glandulifera significantly reduced population growth rate of the water flea Daphnia magna and the green alga Acutodesmus obliquus, both keystone species of lakes and ponds. Laboratory experiments using the main allelochemical released by I. glandulifera, 2‐methoxy‐1, 4‐naphthoquinone, revealed negative fitness effects in D. magna and A. obliquus . Our findings show that allelochemicals from I. glandulifera not only reduce biodiversity in terrestrial habitats but also pose a threat to freshwater ecosystems, highlighting the necessity to incorporate cross‐ecosystem effects in the risk assessment of invasive species. Abstract : Invasive plant species are a major threat to ecosystems. We could show that allelochemicals from I. glandulifera, an invasive terrestrial plant species, not only reduce biodiversity in terrestrial habitats but also pose a threat to freshwater ecosystems, highlighting the necessity to incorporate cross‐ecosystem effects in the risk assessment of invasive species.